Incidence of hepatitis A in children with acute icteric hepatitis of district Shopian of Kashmir - Lone, Rais Ahmad; Khurshid, Ishfaq; Mushtaq, Azhar (International Journal of Contemporary Pediatrics, 2022)
Background: Viral hepatitis is a major health problem worldwide. It is caused by at least five hepatotropic viruses, hepatitis A virus being the commonest one. The virus is responsible for most forms of acute benign hepatitis, although fulminant hepatic failure can occur. HAV spreads mainly through the fecal-oral route and hence is preventable by precautionary methods. Hepatitis A vaccine is available and highly effective in preventing disease. Objective of current study was to find the incidence of hepatitis A in children with features of acute icteric hepatitis of district Shopian of Kashmir. Methods: We sampled 83 children aged above 1 year to 17 years who attended the hospital for different features suggestive of hepatitis and evaluated them after proper and detailed history followed by relevant investigations and serology. Cases were labelled positive or negative on the basis of HAV IgM antibody. Results: We had 83 cases, 36 were boys (43.37%) and 47 were girls (56.62%). The girls made just more than a half of the cases and the boys just below half the cases. 13.25% (11 cases) were aged 1 to 4 years (none was below 2 years), 32.53% (27) were 4 to 7years, 32.53% (27) were 7 to 10 years, 16.87% (14) were 10 to 13 years, only 4.82% (4 cases) reported were 13 to 17 years. All 83 proved to be hepatitis A (100%). Conclusions: This study found that the incidence of hepatitis A in children with features of acute icteric hepatitis is very high in the children of district Shopian & a survey with a very large sample size will be ideal.